Manajemen Program Trilingual di Sekolah Islam - Puput Mulyono; Singgih Purnomo (Universitas Muhammadiyah Manado, 2024)
The background that encourages this research is that basically the trilingual program is needed to equip students to have global competitiveness because of their proficiency in English and Arabic. The purpose of this study is to examine the implementation, evaluation, and find out the difficulties and obstacles in the implementation of the bilingual program based on holistic education at Al-Azhar Islamic School Sukoharjo. This research method is descriptive qualitative. This research uses data collection techniques in the form of interviews, observations, documentation, and questionnaires. While the data analysis technique includes three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the trilingual program is in the form of using English in English subjects. Evaluation of the bilingual program based on holistic education includes exercise, practice, and enrichment. The difficulties and obstacles faced are that students do not fully understand the learning process using English. The conclusion of this study is that the implementation of a holistic education-based bilingual program is carried out through the implementation of three curricula with different approaches, recruitment of teachers who have English language skills, and the use of mixed language in the implementation of learning. Evaluation of teachers is conducted through monthly meetings by the school management. Meanwhile, evaluation for students is carried out through daily assignment assessments, mid-semester exams, and end-of-semester exams. Difficulties and obstacles encountered are the different abilities of students, the different carrying capacity of each family, and the existence of students who do not understand the benefits of language.